Pectoralis Major Tendon Tear: A Critical Analysis Review. Issue 8 (August 2021) - Magone, Kevin; Ben-Ari, Erel; Gyftopoulos, Soterios; Virk, Mandeep
Abstract : Pectoralis major (PM) tendon tears are predominantly seen in young men, and the majority of tears occur as tendon avulsions involving the sternal head. Weightlifting, specifically bench-pressing, and sporting activities with eccentric overloading of the PM tendon are the 2 most common activities that result in PM injury. Early surgical repair or reconstruction should be offered to younger, active patients with a complete PM tear; the majority of the patients undergoing surgical repair achieve good-to-excellent outcomes. Nonsurgical treatment of a complete PM tear is an option but will result in cosmetic deformity and a deficit in adduction strength of the arm. Outcomes after nonsurgical treatment of complete PM tears are less satisfactory than those obtained after surgical treatment. Currently, there is no consensus on the chronological definition of PM tears (acute versus chronic), the critical time limit for performing surgical repair, the ideal fixation device (cortical button, bone tunnel, or suture anchors), the indications for allograft use, and the ideal rehabilitation protocol after treatment of PM tears.